High catalytic activity in aqueous heck and Suzuki–Miyaura reactions catalyzed by novel Pd/Ln coordination polymers based on 2, 2′-bipyridine-4, 4′-dicarboxylic acid as a heteroleptic ligand. (5th September 2016) - You, Lixin; Zhu, Wenli; Wang, Shuju; Xiong, Gang; Ding, Fu; Ren, Baoyi; Dragutan, Ileana; Dragutan, Valerian; Sun, Yaguang
Graphical abstract: Four 2D heterobimetallic coordination polymers [LnPd(BPDC)5/2 (H2 O)·4H2 O] n (Ln = Nd (1 ), Sm (2 ), Eu (3 ) and Dy (4 ); H2 BPDC = 2, 2′-bipyridine-4, 4′-dicarboxylic acid) have been synthesized and characterized. The compounds1 –4 displayed high activity in Heck and Suzuki–Miyaura cross-coupling reactions under aqueous conditions. Abstract: Four novel heterobimetallic Pd/Ln coordination polymers, [LnPd(BPDC)5/2 (H2 O)·4H2 O] n (Ln = Nd (1 ), Sm (2 ), Eu (3 ) and Dy (4 ); H2 BPDC = 2, 2′-bipyridine-4, 4′-dicarboxylic acid), have been synthesized under hydrothermal conditions and characterized by X-ray crystallography, thermogravimetric (TG) analysis, powder X-ray diffraction (PXRD) spectroscopy, elemental analysis and infrared spectroscopy (IR). Single-crystal X-ray diffraction analysis revealed that compounds1 –4 are isomorphous, having a 2D layer structure with a triclinic crystal system. The new Pd/Ln coordination polymers displayed impressively high activity in Heck and Suzuki–Miyaura cross-coupling reactions under eco-friendly, aqueous conditions.